827 nm bragg grating sensor in multimode microstructured polymer optical fibre - Kalli, Kyriacos; Johnson, Ian P.; Webb, David J. (My University, 2010)
Reported is the fabrication and characterisation of a Bragg grating in multimode microstructured polymer optical fibre with a Bragg wavelength of 827nm. This is the smallest Bragg wavelength reported to date for a polymer optical fibre grating, and the relatively low loss of the fibre at this wavelength considerably enhances the utility of the device compared to gratings at longer wavelengths.
Keywords: Fiber optics; Optical fibers; Polymers; Bragg gratings; Fibers